On total moduli of continuity for $2π$-periodic functions of two variables in the space $L_{2,2}$ - Vakarchuk, M. B.; Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The description of the total moduli of continuity of $2π$ -periodic functions of two variables are obtained in the space $L_{2,2}$.The proposed description can be regarded as an extension of the famous results by O. V. Besov, S. B. Stechkin, V. A.Yudinon the moduli of continuity in $L_{2}$ in the two-dimensional case.